SOCIAL AND LEGAL PROTECTION IN THE SOCIAL WORK PRACTICE: THEORETICAL ANALYSIS (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with a concept and essence of social and legal protection in social service. The author defines the approaches to the terms "social protection" and "legal protection" in broad and narrow senses. The article looks over the expediency of the terms and the contexts of their usage. Social and legal protection is suggested to be defined as a complex of national social institutions and NGO means to providing the convenient living conditions, fulfilling of needs, rights realization opportunities of individuals and different social group. Administrative, legal and community social service institutions, which are involved in legal, educational and cultural activities and take part in realisation of social services programs targeted on personal adaptation, social protection and providing other social services are considered the subjects of social and legal protection. Main emphasize is being set on the strengthening of interaction between social and legal elements of social worker competency.
Keywords: social and legal protection; social work; social worker; social and legal competence; social services.